Technical Report: The Polomac approach to fusion energy (The Journal of Technological and Space Plasmas, 2024)
Deutelio is a private initiative promoting an alternative path to fusion energy. The Tokamak research line pursued worldwide since 1970 met several difficulties, heavily jeopardising the objective of commercial energy production from fusion before 2050, as a support to the global effort towards Net Zero Emissions. As a result, new plasma magnetic confinement concepts, such as Stellarators or overlooked alternatives like the poloidal confinement are being pursued to achieve  more efficiency and better performance.The Polomac is a poloidal magnetic configuration where the outboard magnetic lines are deviated aside together with the plasma, to open some accesses to the dipole coils located inside the plasma. These accesses, called magnetic tunnels, are used to support, feed and cool the dipole coil. They avoid the impact with plasma which led to abandon past poloidal experiments, despite their good stability and confinement efficiency.The poloidal confinement can achieve Deuterium-Tritium reactor conditions with a magnetic field 3 times weaker than the Tokamak, in steady state rather than pulsed. With the same high field as in the Tokamak the poloidal confinement can achieve Deuterium-Deuterium reaction, thus avoiding the development of the breeding blanket to produce the Tritium.This paper presents the Polomac system, explains the development strategy of Deutelio through a small prototype focused to tune and assess the magnetic tunnels, and describes the possibility of deuterium-deuterium reaction.
Keywords: Deutelio; Polomac; Poloidal magnetic confinement; high plasma pressure; fusion energy; DD reaction; high density plasma; high temperature plasma